Ecological and economic aspects of the application of sewage sludge in energetic plant plantations - a SWOT analysis = Ekologiczno-ekonomiczne aspekty zastosowania osadów ściekowych na plantacjach roślin energetycznych - analiza SWOT - Wójcik, Marta; Stachowicz, Feliks; Masłoń, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sewage sludge management in Poland is a relatively new field of waste management called ?in statu nascendi?, the standards of which have not been recognized yet. It also requires the implementation of new solutions in the field of sewage sludge. So far, the most popular method of sewage sludge utilization has been landfill disposal.
Keywords: sewage sludge; SWOT analysis; sewage sludge management; energetic plants; osady ściekowe; analiza SWOT; gospodarka osadami ściekowymi; rośliny energetyczne